Effect of industrial revolution on strategic management capabilities with Tawhidic paradigm among companies in Malaysia - Mhd. Sarif, Suhaimi (IIUM Press, International Islamic University Malaysia, 2020)
This study obtained the views of senior managers from companies in Malaysia pertaining to the effect of industrial revolution on strategic management capabilities with Tawhidic paradigm. The study used personal interview method with senior managers of public companies in Malaysia. The results suggested that the effect of industrial revolution on strategic management capabilities with Tawhidic paradigm are in the ability to integrate objectives of companies with humanity and soul enrichment of stakeholders who used to financial gains.